The Influence of Fiki Naki’s Self-Disclosure on Subscribers’ Perceptions - Darmawan, Kevin; Delliana, Santi (Research and Community Service UNIVERSITAS KALBIS, 2024)
All individuals must communicate in the ongoing information exchange process. Indonesian Youtuber Fiki Naki. Fiki Naki has 3.85 million YouTube subscribers as of March 19, 2021. Fiki Naki published “Dayana, Cewek Kazakhstan Yang Ngajak Aku Nikah (Part 1)” on January 11, 2021. The video shows an Indonesian YouTuber meeting a Kazakhstani woman. On January 11, 2021, Fiki Naki reuploaded “Dayana Nungguin Aku di Kazakhstan (Part 2)”. In this second video, Dayana learns that Fiki Naki is an Indonesian YouTuber and resumes her conversation. Dayana mentioned her Indonesian fame and Instagram growth. On January 18, 2021, Fiki Naki re-uploaded his third and fourth videos, “Dayana Cerita Tentang Perasaannya (Part 3)” and “Dayana Sedih Karena Ini… (Part 4),” on YouTube. They talked in this third video to get closer. Fiki Naki asks Dayana personal questions. Their fourth video continues their third. They discuss Dayana's thoughts on Indonesians, who hate and like her. The stimulus-response theory underpins this study. This study examined Fiki Naki's self-disclosure's impact on subscriber perceptions and its degree of influence. This research examines how Fiki Naki's transparency influences subscribers. The researcher will use 4.1 million Fiki Naki YouTube subscribers as of April 30, 2021. This study employed purposive sampling. Since numerous criteria define the sample, this method was chosen: 1. Fiki Naki's YouTube followers. 2. Have they watched Fiki Naki videos with Dayana? Slovin algorithm estimates sample size; with a 5% margin of error, 399.97 is rounded up to 400 respondents.